Autoimmune Encephalitis in Children - Papetti, Laura; Salfa, Irene; Vigevano, Federico; Valeriani, Massimiliano (Journal of Pediatric Infectious Diseases, 2019)
Autoimmune encephalitis (AIE) can produce a very wide range of neuropsychiatric symptoms. A major challenge in diagnosis is that different symptoms may appear at different times and different levels of intensity, so the disease may mimic many other disorders. Pathogenesis is likely to be mediated by antibodies (Abs) to CNS proteins. This article focuses on recent clinical advances, newly characterized Abs, and treatment approaches to these disorders.
Keywords: autoimmune encephalitis; antibodies; childhood